2018
DOI: 10.13189/ujer.2018.060717
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rapid Strength and Shooting Training Applied to Professional Basketball Players on the Shot Percentage Level

Abstract: The aim of this study is to examine the effects of explosive strength and shooting exercises, which were applied for eight weeks before the season in basketball sport branch, on shot percentage level of elite male basketball players. The study was conducted on 13 professional male basketball players (age average; 26.92 ± 3.04) who are actively playing in the Turkish Basketball Super League. The players were taken into pre-season camp for 12 weeks. At the end of the first four weeks, shooting tests (pre-tests) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Some of studies about the skill in psychomotor assess the technique of playing basketball have been done [13]. Most of them develop the test skill in sport skill test.…”
Section: Background Of Studymentioning
confidence: 99%
“…Some of studies about the skill in psychomotor assess the technique of playing basketball have been done [13]. Most of them develop the test skill in sport skill test.…”
Section: Background Of Studymentioning
confidence: 99%
“…Previous studies have shown that players with more training experience had better free-throw performance compared to less-experienced players [12,14]. Moreover, it was shown that explosive strength training of upper and lower limb improves basketball shooting accuracy [7]. In our study, we investigated shooting performance from shorter and longer, as different shooting distances may require different involvement of muscle strength capacities.…”
Section: Discussionmentioning
confidence: 99%
“…RTD-SF has already been shown to be sensitive to changes in neuromuscular function associated with age [2] and disease [6]. As it was shown that explosive strength training positively influences shooting accuracy in basketball players [7], and moreover, there are some indices that maximum strength of elbow extensors is positively associated with shooting accuracy in the three-point shot, our goal was to further investigate the relationship between upper limb strength capacity and shooting performance. We hypothesized that a sport-specific movement that is constantly repeated (such as basketball shooting) might have an influence on strength capacities (k RTD-SF , T MVC , and RTD PEAK ) of the responsible muscle groups, and in addition, it might be dependent on the training history and physical development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of basketball is to provide a good shot to score and to take countermeasures against the rival trying to produce numbers with a shot like himself (Karause, 2008). Shoot is the most important determinant in determining the result of a game, winning the game and establishing superiority (Malone, 2002;Csataljay et al 2013;Haris et al, 2018;Savaş et al, 2018). Shoot is the most difficult skill to develop into the physical skills applied in basketball games (Wisse, 2011).…”
Section: Introductionmentioning
confidence: 99%